2018
DOI: 10.1002/gch2.201800030
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of His‐Au NCs and MES‐Au NCs on the Propagation of Pseudorabies Virus

Abstract: In a previous work, gold nanoclusters (Au NCs) are found to inactivate RNA virus, but the effect of surface modification of Au NCs on its proliferation is still largely unknown. Here, the effect of surface modification of Au NCs on the proliferation of pseudorabies virus (PRV) by synthesizing two types of gold clusters with different surface modification, histidine stabilized Au NCs (His‐Au NCs) and mercaptoethane sulfonate and histidine stabilized Au NCs (MES‐Au NCs), is investigated. His‐Au NCs rather than M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Surface modification plays an important role in the antiviral activity of AuNCs; therefore, researchers modified the surface of AuNCs with two different materials-histidine and mercaptoethane sulfonate. Among these, histidine-stabilized AuNCs showed strong inhibition of the proliferation of pseudorabies virus (PRV) [101,102]. Therefore, AuNPs functionalized with different molecules play critical roles in antiviral activity.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Surface modification plays an important role in the antiviral activity of AuNCs; therefore, researchers modified the surface of AuNCs with two different materials-histidine and mercaptoethane sulfonate. Among these, histidine-stabilized AuNCs showed strong inhibition of the proliferation of pseudorabies virus (PRV) [101,102]. Therefore, AuNPs functionalized with different molecules play critical roles in antiviral activity.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…His-Au NCs and MES-Au NCs were synthesized as previously reported method. 32,33 The high-resolution transmission electron microscopy (HR-TEM) analysis showed no obvious difference between His-Au NCs and MES-Au NCs in morphology ( Fig. S1a and b †).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, 32 the effects of MES-stabilized Au NCs (MES-Au NCs) and histidine-stabilized Au NCs (His-Au NCs) on the propagation of pseudorabies virus were investigated. Occasionally, we found that the uorescence intensity of His-Au NCs could be enhanced aer adding MES.…”
Section: Introductionmentioning
confidence: 99%
“…5). In order to explore the effect of surface modification upon the antiviral performance of Au NCs, we synthesized two types of gold clusters with different surface modification: histidine stabilized Au NCs (His-Au NCs), and mercaptoethane sulfonate and histidine stabilized Au NCs (MES-Au NCs) [81]. It is His-Au NCs rather than MES-Au NCs that were found to strongly inhibit the proliferation of PRV, as indicated by the results of plaque assay, confocal microscopic analysis, quantitative real-time polymerase, Western blot assay, and chain reaction assay.…”
Section: Gold Nanoclustersmentioning
confidence: 99%